Silicon, endophytes and secondary metabolites as grass defenses against mammalian herbivores - Huitu, Otso; Forbes, Kristian M.; Helander, Marjo; Julkunen-Tiitto, Riitta; Lambin, Xavier; Saikkonen, Kari; Stuart, Peter; Sulkama, Sini; Hartley, Sue (Frontiers in Plant Science, 2014)
Grasses have been considered to primarily employ tolerance in lieu of defense in mitigating damage caused by herbivory. Yet a number of mechanisms have been identified in grasses, which may deter feeding by grazers. These include enhanced silicon uptake, hosting of toxin-producing endophytic fungi and induction of secondary metabolites. While these mechanisms have been individually studied, their synergistic responses to grazing, as well as their effects on grazers, are poorly known. A field experiment was carried out in 5 × 5 m outdoor enclosures to quantify phytochemical changes of either endophyte-infected (E+) or endophyte-free (E-) meadow fescue (Schedonorus pratensis) in response to medium intensity (corresponding with densities of ca. 1200 voles / ha for 5 weeks during 3 months) or heavy intensity (ca. 1200 voles / ha for 8 weeks during 3 months) grazing by a mammalian herbivore, the field vole (Microtus agrestis). A laboratory experiment was then conducted to evaluate the effects of endophyte infection status and grazing history of the grass diet on vole performance. As predicted, grazing increased foliar silicon content, by up to 13 %. Grazing also increased foliar levels of phosphorous and several phenolic compounds, most notably those of the flavonols isorhamnetin-diglycoside and rhamnetin derivative. Silicon concentrations were consistently circa 16 % higher in E+ grasses than in E-grasses, at all levels of grazing. Similarly, concentrations of chlorogenic acid derivative were found to be consistently higher in E+ than in E- grasses. Female voles maintained on heavily grazed grasses suffered higher mortality rates in the laboratory than female voles fed ungrazed grass, regardless of endophyte infection status. Our results conclusively demonstrate that, in addition to tolerance, grasses employ multi-tiered, effective defenses against mammalian grazers.